INSTITUSI PENDIDIKAN ISLAM ANAK USIA DINI - Lydia Sartika; Dianty Wulandari (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Early childhood education institutions (PAUD) are places or institutions specifically designed to provide education and care for children aged 0 to 6 years. The function of PAUD educational institutions is to help create a strong foundation for children's future academic, social, emotional and life skills development.